2014
DOI: 10.1371/journal.pone.0111706
|View full text |Cite
|
Sign up to set email alerts
|

The First Cytogenetic Data on Strumigenys louisianae Roger, 1863 (Formicidae: Myrmicinae: Dacetini): The Lowest Chromosome Number in the Hymenoptera of the Neotropical Region

Abstract: In the present study, the first cytogenetic data was obtained for the ant species Strumigenys louisianae, from a genus possessing no previous cytogenetic data for the Neotropical region. The chromosome number observed was 2n = 4, all possessing metacentric morphology. Blocks rich in GC base pairs were observed in the interstitial region of the short arm of the largest chromosome pair, which may indicate that this region corresponds to the NORs. The referred species presented the lowest chromosome number observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 31 publications
3
9
0
2
Order By: Relevance
“…Strumigenys louisianae from the Amazon rainforest showed 2n = 26 chromosomes and karyomorphometrical analysis revealed that the karyotype consists of m, sm and st chromosomes with diploid karyotypic formula 12m + 12sm + 2st (Table 2, Figure 2). The species presented a quite distinct chromosome number from that of the Atlantic rainforest population (2n = 4, all metacentrics, see Alves-Silva et al, 2014). The chromosome size of the largest chromosome pair (the single st pair) showed its size 2.5x larger than the second largest chromosome pair (1 st m pair) corresponding to a notable size difference in the karyotype (Table 2, Figure 3).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Strumigenys louisianae from the Amazon rainforest showed 2n = 26 chromosomes and karyomorphometrical analysis revealed that the karyotype consists of m, sm and st chromosomes with diploid karyotypic formula 12m + 12sm + 2st (Table 2, Figure 2). The species presented a quite distinct chromosome number from that of the Atlantic rainforest population (2n = 4, all metacentrics, see Alves-Silva et al, 2014). The chromosome size of the largest chromosome pair (the single st pair) showed its size 2.5x larger than the second largest chromosome pair (1 st m pair) corresponding to a notable size difference in the karyotype (Table 2, Figure 3).…”
Section: Resultsmentioning
confidence: 92%
“…In this study, we described the karyotype of S. louisianae from Oiapoque, state of Amapá, Brazil, in north-eastern Amazonia and compared it with the available karyotype from the population of the Atlantic rainforest (Alves-Silva et al, 2014). We also highlighted morphological differences between the two populations and discussed the taxonomic importance of our results.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…The huge variation in chromosome number ranging from 2n = 2 to 2n = 120 (Lorite & Palomeque, 2010) may provide good models to investigate the role of chromosomal variation in speciation. The Attini tribe alone currently comprises 48 genera with a total of 2.703 valid species, but there is cytogenetic information for only 21 genera (Cardoso et al, 2018) with karyotypes ranging from 2n = 4 to 2n = 64 (Alves-Silva et al, 2014;Murakami et al, 1998;Barros et al, 2013;Mariano et al, 2019;Cardoso & Cristiano, 2021). This means that the karyotypes of 56.25% of the Attini genera, such as Blepharidatta, are unknown.…”
Section: Introductionmentioning
confidence: 99%